El impacto a la aplicación de los beneficios tributarios de una persona con discapacidad de ha realizado declaraciones del impuesto a la renta - Vargas Castillo, María José (2015)
This research aims to measure the impact on the application of tax benefits at the time of the settlement of income tax, since they have established special deductions that reduce the payment of this tax, therefore considered the deductions of people with disabilities. The research requires research techniques such as document Bibliographic - that through books, magazines, scientific articles, let us know the phenomenon, extract real cases to be compared in order to study and to establish research results , which show that there is an economic impact on the declaration of income tax for persons with disabilities as to which deductions can benefit not allow them to generate a tax caused, or in other cases may be lower, leaving a balance of tax credit for withholding that are made, which have the right to demand the corresponding claim.